Răspuns :
[tex] \frac{( {3}^{ - 2} \times 241) }{(81 \times {9}^{ - 2}) } = \frac{ \frac{1}{ {3}^{2} } \times 241 }{81 \times {9}^{ - 2} } = \frac{ \frac{1}{9} \times 241 }{81 \times {9}^{ - 2} } = \frac{ \frac{241}{9} }{81 \times {9}^{ - 2} } = \frac{ \frac{241}{9} }{81 \times \frac{1}{ {9}^{2} } } = \frac{ \frac{241}{9} }{81 \times \frac{1}{81} } = \frac{ \frac{241}{9} }{1} = \frac{241}{9} [/tex]
(3⁻² * 241 ) / (81*9⁻² ) =
( 1/3^2 × 241) / ( 81 × 1/9^2) =
241/9 : 81/81 =
241/9 : 1 =
241/9 =
26,(7)
_____
( 1/3^2 × 241) / ( 81 × 1/9^2) =
241/9 : 81/81 =
241/9 : 1 =
241/9 =
26,(7)
_____